Watertown Community Path: Linking Watertown's Past to its Future (Report). - Carter, Kristopher.; Giambrone, Eric.; Kim, Eunice.; Moon, Michelle.; Tommee, Jong Wai. (Tufts University. Tisch Library., 2018)
2010 M.A. in Urban and Environmental Policy and Planning Field Project. Clients: Town of Watertown Department of Community Development and Planning (primary client); Watertown Citizens for Environmental Safety; Watertown Bicycle and Pedestrian Committee.